HUBUNGAN DUKUNGAN KELUARGA DENGAN PERILAKU PENGENDALIAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS MAESAN: Relationship Between Family Support and Hypertension Control Behavior in The Elderly in The Work Area of Maesan Public Health Center - Intania; Dewi, Sofia Rhosma; Elmagfhuroh, Dian Ratna (Forind Press, 2024)
Hypertension is a common degenerative disease that attacks the elderly. One of the factors that influence the occurrence of hypertension in the elderly is an unhealthy lifestyle and lack of family support so that self-management in the elderly is not carried out properly. Identifying the relationship between family support and hypertension control behavior in the elderly in the Maesan Health Center Work Area is the purpose of this study using a correlational design method with a Cross-Sectional approach. The sample in this study was the elderly in the Maesan Health Center Area with a total of 143 respondents obtained by purposive sampling technique. The results of family support are mostly in the good category as many as 70 respondents (49.0%). Hypertension control behavior in the elderly is mostly in the good category as many as 73 respondents (51.0%). The results show that there is a relationship between family support and hypertension control behavior in the elderly in the Maesan Health Center Work Area, the better the support given by the family to the elderly, the better the hypertension control behavior in the elderly. Suggestion for the elderly it is expected that the elderly who suffer from hypertension will implement healthy living behaviors.